SPECIFICS OF MYOCARDIAL INFARCTION IN OBESITY - G. A. Chumakova; A. P. Pokutnev; N. G. Veselovskaya (Российский кардиологический журнал)
The article is focused on the issue of prediction of acute coronary syndrome onset (ACS) and its clinical course specifics in patients with various obesity grades. The phenomenon of “obesity paradox” is taken in ACS, and several possible explanations are given. The data is provided, on the closer relation of the ACS risk with such criteria for obesity as waist circumference and index waist/hip circumference, as these parameters indirectly point on the presence of visceral obesity. The results presented, of the studies on close relation of epicardial fat tissue with its neurohumoral actions in ACS risk.